Comparative analysis of performance indicators between winning and losing team in female handball Olympic games tournament 2012 / Siti Irdina Najwa Mohd Sohim ... [et al.]. - Mohd Sohim, Siti Irdina Najwa; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Raja Hussain, Raja Nurul Jannat; Shari, Maisarah; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Handball is a fast-paced team sport that requires a combination of physical strength, technical skills, and strategic play. The outcome of a match, whether a team wins or loses depends on various factors, including team performance, tactical execution, and psychological resilience. Winning in handball is often associated with superior teamwork, effective offensive and defensive strategies, and high levels of player motivation [1]. The purpose of this study was to analyse a comparative analysis of performance indicators between winning and losing team in female handball Olympic games 2012. Performance indicators pass rate, defensive block, turnovers, foul count, goalkeeper saves, rebounds, shot accuracy and penalty efficiency [2]. The problem statement on offensive play in handball provides valuable insight but has notable limitations. The reliance on basic statistics like the Mann-Whitney U test may oversimplify the complex dynamics of handball games [3].